2000
DOI: 10.1021/jo000752b
|View full text |Cite
|
Sign up to set email alerts
|

Computational Studies on the BF3-Catalyzed Cycloaddition of Furan with Methyl Vinyl Ketone:  A New Look at Lewis Acid Catalysis

Abstract: Transition structures for both uncatalyzed and BF3-catalyzed Diels-Alder reactions involving furan and methyl vinyl ketone have been determined at the hybrid DFT (B3LYP/6-31G*) level of theory. The transition structures are predicted to be relatively concerted and highly asynchronous in all cases. A subsequent bond-order analysis has been carried out at the MP2/6-31G*//B3LYP/6-31G*. The role of the Lewis acid and the origin of the endo selectivity have been discussed in terms of the nature and number of intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…We did not find any low-lying [2 + 4] hetero-DA transition states that are sometimes artifacts of low-level Hartree-Fock calculation. 28,29,31,32 Recent studies by Silva et al, 33 Tanaka and Kanemasa, 34 and Roberson et al 35 also suggested that Lewis acid catalyzed cycloaddition reactions might occur through a stepwise mechanism. However, their semiempirical and Hartree-Fock calculation very likely overestimated the energy barriers of the second TS due to the implicit treatment or omission of the electron correlation energies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We did not find any low-lying [2 + 4] hetero-DA transition states that are sometimes artifacts of low-level Hartree-Fock calculation. 28,29,31,32 Recent studies by Silva et al, 33 Tanaka and Kanemasa, 34 and Roberson et al 35 also suggested that Lewis acid catalyzed cycloaddition reactions might occur through a stepwise mechanism. However, their semiempirical and Hartree-Fock calculation very likely overestimated the energy barriers of the second TS due to the implicit treatment or omission of the electron correlation energies.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with several earlier studies. [25][26][27][28][29] The MP2/6-31+G* method predicted bond lengths of 2.149 and 2.522 Å for the forming C-C bonds in the endo-cis TS of the CP/MVK system and 2.152 and 2.596 Å for the CH/MVK system. These values are compared to 2.279 Å for the parent DA reaction (1,3-butadiene + ethylene) calculated at the same level of theory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction of methyl vinyl ketone with furan catalyzed by BF 3 was studied by Babiano et al [22]. The transition states predicted were also relatively concerted and highly asynchronous for all the reaction paths studied.…”
Section: Carbo-diels-alder Reactions 309mentioning
confidence: 99%
“…[53] As shown in Figure 1( Colored pictures are shown in Supporting Information), distortion/interaction analysis( also knowna st he Activation Strain Model) [54] is ap owerful toolf or understanding reactivity in bimolecular reactions;i nt his model,t he activation energy (DE°)i sd ivided into ad istortion energy term (DE dist )a nd an interaction energy term (DE int ). [55][56][57][58][59][60][61][62][63][64][65][66] The distortion energy is the energy needed to distort reactants to the geometry they adopt in the transitions tate and the interaction energy is the energy change upon interaction of the two distorted fragments.T he distortion/interactiona nalysis is frequentlye mployed to explain the reactivity observed in 1,3dipolar cycloadditionsa nd other cycloaddition reactions. [67][68][69] The reactivities of these types of reactionsc orrelate wellw ith the distortion energies due to the small differences in the interaction energies.…”
Section: Introductionmentioning
confidence: 99%